2012
DOI: 10.1177/2156587211436235
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture at Zusanli (ST-36) Restores Impaired Interstitial Cells of Cajal and Regulates Stem Cell Factor Pathway in the Colon of Diabetic Rats

Abstract: The present study determined the effects of electroacupuncture on interstitial cells of Cajal and investigated whether changes in the stem cell factor pathway were involved. Animals were assigned to normal, diabetic, diabetic plus sham stimulation, diabetic plus low-frequency stimulation, and diabetic plus high-frequency stimulation groups. Electroacupuncture was performed daily for 8 weeks. In vitro contractility of colonic muscle strips were studied. Expression of c-kit (the marker of interstitial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Forrest et al found that in the colon, ICC-IM as well as ICC-SMP were affected most severely [ 8 ]. Moreover, our recent studies have revealed that EAS can increase the density of ICC and repair the nervous apparatus [ 6 , 17 ], so we choose to observe the alteration of ICC-IM based on the preliminary experiment. In the present study, we also showed that the density and ultrastructure of ICC-IM were elevated significantly in the EAS group, especially the HEA group, which may be responsible for its efficacy in regulating colonic motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forrest et al found that in the colon, ICC-IM as well as ICC-SMP were affected most severely [ 8 ]. Moreover, our recent studies have revealed that EAS can increase the density of ICC and repair the nervous apparatus [ 6 , 17 ], so we choose to observe the alteration of ICC-IM based on the preliminary experiment. In the present study, we also showed that the density and ultrastructure of ICC-IM were elevated significantly in the EAS group, especially the HEA group, which may be responsible for its efficacy in regulating colonic motility.…”
Section: Discussionmentioning
confidence: 99%
“…Rangwala et al has showed that EAS is a safe and effective method for treatment of constipation without any adverse effect [ 5 ]. Recently, our study showed that EAS at acupoint ST-36 can increase the density of interstitial cells of Cajal (ICC) and upregulate the expression of colonic ICC [ 6 ]. However, the potential roles of EAS on colonic motility and ICC in diabetic constipation rats have scarcely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our immunohistochemical study also provided evidence that RC treatment can regulate the SCF/SCFR pathway and restore the expression of ICCs in the gastric antrum of rats. Additionally, data indicate that the expression of SCF, particularly M-SCF, induces prolonged activation and longer lifespan of SCFR (Xu et al, 2012;Miyazawa et al, 1995). Chen et al (2013) demonstrated a significant correlation between the expression of S-SCF and M-SCF and SCFR expression (Chen et al, 2013).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 89%
“…survival, proliferation, and differentiation (Torihashi et al, 1999;Tong et al, 2010). Previous studies have shown a significant decrease in SCF and SCFR expression in diabetic animals (Horváth et al, 2006;Lin et al, 2010;Xu et al, 2012). Fortunately, some studies have indicated that treatments can increase the expression of SCF and SCFR in rat models (Wang et al, 2008;Lu et al, 2013).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%